Payload characteristics related to mission profile of unmanned aerial vehicle systems: a preliminary study / Abu Zaid Bakar and Khairul Dahri - Bakar, Abu Zaid; Dahri, Khairul (2006)
This paper is a preliminary report of an ongoing study and research of the Unmanned Aerial Vehicle (UAV). The UAV is commonly used as the most effective reconnaissance or tactical method in any particular ,country, Currently, in the world, there are hundreds of flying UAVs, which had been developed by the government of that particular country or any private company, to compete for the most unique and versatile product for its own usage or marketing purposes, The study involves a research on the payload characteristics, capabilities and categories, which are related to a specific mission profile. Most of the common payload available in the market will be discussed, Various types of mission profile that might further improve the system efficiency will be proposed.